Penampilan Galur Harapan Mutan Dihaploid Padi Tipe Baru di Sulawesi Selatan - Dewi, Iswari Saraswati; Lestari, Endang Gati; ,, Chaerani; Yunita, Rossa (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2015)
ABSTRACTSouth Sulawesi is known as one of national rice production centers. However, average productivity of rice varieties planted in that area (4.43 ton ha-1) is lower than those of rice productivity in Java (5.25 ton ha-1). The aims of this research were to evaluate agronomic characters and adaptation of 7 dihaploid mutant advanced lines of new plant type (DH-NPT) of rice at several locations in South Sulawesi. The research was conducted in 2012 at Maros, Gowa, Barru, and Pangkep. The experiments were conducted in randomized complete block design with 3 replications nested in locations. Treatment consisted of 7 DH-NPT of rice, i.e., BIO-MF115, BIO-MF116, BIO-MF125, BIO-MF130, BIO-MF133, BIO-MF151, BIO-MF153, and control varieties i.e., Fatmawati, Ciherang, and Inpari13. The results indicated that in general the lines had medium height (102.77-110.23 cm), moderate productive tiller (9-16 tiller per hill), moderate days to flower (50%), i.e., 73-76 days after sowing (DAS), earlier days to harvest (103-110 DAS), moderate panicle length (28.35-29.31 cm), large number of grain per panicle (> 250 grains) with moderate panicle fertility (63-70%), moderate 1,000 grain weight, i.e., 26.51-27.75 g, and high yield (7.51-8.09 ton ha-1). Four lines, i.e., BIO-MF116, BIO-MF130, BIO-MF151, and BIO-MF153 were stable and had wide adaptability. Other lines, i.e., BIO-MF125 and BIO-MF133 were sensitive to environmental changes, therefore they were classified as specifically adapted to favorable environment; while BIO-MF115 was not sensitive to environmental changes, and therefore it was adapted to non-favorable environment.Keywords: adaptation, agronomic characters, rice mutant